Hadhkii madoobaa - Al-Kiilaani, Najiib,Aadan Xassan Aadan (Institut des langues, République de Djibouti, 2008)
Historical play
Keywords: Anthologie; Theaterstück; Texts; Somali; Drama; Somali language; Somali (Langue); Ethiopia; drama (form)